Hubungan Antara Perceived Social Support Dengan Self Esteem Pada Remaja Penyandang ADHD - Farra Dyba Faleria Akuan; Alabanyo Brebahama (Fakultas Psikologi Universitas YARSI, 2025)
Based on Law Number 8 of 2016, ADHD can be classified as a type of mental disability along with Spectrum Autism, Bipolar disorder and so on. ADHD tends to experience inattentive, impulsivity and hyperactivity syndromes that impact their academic aspects at school. Meanwhile, the participation of people with ADHD either in socializing or in the community will pose challenges, namenlu pressure in socializing and the extent of peer acceptance of people with ADHD. While social support has an important role in the development of self esteem, especially for adolescents. This study aims to look at the relationship between perceived social support and self esteem in adolescents with ADHD. This study uses quantitative methods and purposive sampling. The measuring instruments used in this study are Multidimensional Perceived Social Support (MSPSS) and Rosenberg Self Esteem Scale (RSES). The participants in this study were 27 adolescent participants with ADHD who were in the Jabodetabek area. The results obtained are perceived social support in the friendship dimension (friends) has a significant positive relationship with self esteem in adolescents with ADHD (rs = 0.592, p> 0.05). Meanwhile, the other two dimensions of perceived social support, namely family and significant others, do not have a significant positive relationship with self esteem in adolescents with ADHD.